Pengaruh Ketidakamanan Kerja, Keterlibatan Karyawan dan Dukungan Organisasi Terhadap Kinerja Karyawan Dengan Komitmen Organisasional Sebagai Variabel Intervening Pada Karyawan Bagian Produksi Bulu Mata Palsu PT. Cosmoprof Indokarya di Kabupaten Banjarnega - Tyasih Sukma Pawestri; Ari Pradhanawati (Universitas Diponegoro, 2018)
The performance of employees the production of eyelashes PT. Cosmoprof Indokarya shown at an average of the results of each employee in the years 2013-2015 tends to fluctuate. The target of production is set by the company is 1.56 million pairs of eyelashes, but only about 1.4 million pairs of eyelashes can be produced. To deal with the problem is to determine what factors are causing the employee's performance did not reach the target. The high levels of stress and perceived environmental changes employees will create a sense of insecurity that can affect the performance degradation. Lack of organizational support received by employees will affect their performance. When employees are participating in the work and do not have a strong desire to survive in the organization will decrease the performance of the employee. This is also shown by the employee turnover rate of 20% by year. This study aims to identify and analyze the effects of job insecurity, employee engagement, organizational support and organizational commitment to employee performance and organizational commitment partially as an intervening variable. Researchers ask 10 (ten) hypothesis in this study. This type of research is a quantitative research study classification based on objective being explanatory, where statistics were used to analyze the sample data and results will be generalizable to populations where samples were taken. The population in this study were all employees of the production PT.Cosmoprof Indokarya as many as 941 employees and the number of samples 91 employees. Data were analyzed using SEM-PLS and use data analysis tools SmartPLS 3.0. The data analyzed comes from distributing questionnaires to employees. Results of testing the coefficient of SEM analysis showed that: (H1) is rejected; (H2) is received; (H3) is received; (H4) is received; (H5) is received; (H6) was rejected; (H7) is received; (H8) is rejected; (H9) was rejected; (H10) is rejected. The results of the study explains there are some weak indicators of each variable job insecurity, employee engagement, organizational support, organizational commitment, and employee performance. It is recommended that companies to review, evaluation, and give motivation and training on employees in order to improve their capabilities.